DESAIN PENGELOLAAN KEUANGAN PARTAI POLITIK BERBASIS DEMOKRASI MENUJU KEMANDIRIAN PARTAI POLITIK - Didik Sukriono (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
This article discussed fundamental issues about the financial management of political parties and provided a solution to the problem through a design for the financial management of democratic political parties. The method used a conceptual approach. The results showed that the negative impacts that occur when financial management was bad would affect its contribution to the people. What’s more when political parties have limitations in terms of structural and financial. Structural limitations were characterized by weak networks of work and organizations and oligarchic leadership. While financial limitations were characterized by political party financial dependence on donors so that political parties tend to rank the interests of contributors and forget the interests of the community. Large donors occupy strategic positions in the management of political parties or even become determinants of political party policies. For this reason, a political party financial management was needed in a democratic way and the independence of political parties becomes a necessity to realize the role and function of political parties.DOI: http://dx.doi.org/10.17977/um019v3i12018p037